Incidence of low back pain among janitorial workers in Hulu Langat, Selangor / Nurul Ain Izzati Hamade ... [et al.] - Hamade, Nurul Ain Izzati; Azman, Nur Atiqah; Jasni, Sitii Hazwaanii; Wahab, Rosilah; Murad, Mohd Suleiman; Masuri, Mohamad Ghazali; Sultan Ibrahim, Syamsul Anwar; Abdul Zalif, Nurul Ku Harmila (Faculty of Health Sciences, Universiti Teknologi MARA, 2024)
Low back pain (LBP) is a feeling of discomfort or stiffness in the lower back caused by poor work posture, lifting, bending, and other physically challenging tasks. It is one of the musculoskeletal disorders that has been well-studied in various occupational groups, such as farmers, medical staff, truck drivers, and janitors. This study explored the incidence of LBP and how demographic background influences the LBP among janitors in Hulu Langat, Selangor. A cross-sectional study was conducted among 120 janitorial workers in Hulu Langat, Selangor, aged between 25 and 44 years old that was collected through an online questionnaire. Respondents were assessed on a brief working background and the Malay-Standardized Nordic Musculoskeletal Questionnaire. More than half of janitorial workers, ranging 52 to 67 percents suffered LBP with most reported pain areas are at the neck, elbow, and lower back region of the body. To conclude, these body regions were significantly impacted during repetitive activities that involve lifting, flexing, and twisting the trunk during janitorial works. This shows the need to provide ergonomic education and training to improve the workers’ awareness about appropriate work hazards and injuries, potentially reducing the deterioration of prolonged LBP and other occupational hazards among janitors.